Economic Study of Sharia Factoring: A Comparative Review Based on Fikih Muamalah and Fatwa DSN-MUI No. 67 Year 2008 - Pebriani Pebriani; Melia Rosa (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The purpose in study This is for analyze factoring receivables perspective economy as well as comparison factoring receivables based on jurisprudence muamalah and DSN-MUI regulation Number 67 of 2008. In the business world, business actors busines and company always want to to smoothen goods production, so that can increase profit and speed up capital turnover which in turn will push growth economy. With the more height needpublic to goods, then cause Lots company to provide fresh funds obtained from institution factoring receivables (factoring). As one of the alternative financing, factoring receivables Not yet as popular as with type funding others. even though factoring receivables This Enough promising especially at the time the occurrence crisis economy. Therefore, that activity factoring receivables is one of alternative obtain funds for companies that need it. Concept factoring sharia receivables in the DSN-MUI fatwa use contract please bill ujrah. While draft factoring sharia receivables in jurisprudence transactions use contract hiwalah. Both own similarity in aspect definition and mechanism.